Degradation of Lithium-Ion Batteries in an Electric Transport Complex; Energies; Vol. 14, iss. 23 - Shchurov N. I. Nikolay Ivanovich; Dedov S. I. Sergey Igorevich; Malozemov B. V. Boris Vitaljevich; Shtang A. A. Aleksandr Aleksandrovich; Martyushev N. V. Nikita Vladimirovich; Klyuev R. V. Roman Vladimirovich; Andriyashin S. N. Sergey Nikolaevich (2021, 2021)
Title screen